Dinamika Konflik Antara Pedagang Dan Pengelola Pasar Dalam Pembangunan Lokal Baru Di Pasar Pagi Betung Kabupaten Banyuasin - Amelia, Rika; Juainah, Norma; Mirza, Ibrahim Miftafariz (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the dynamics of conflict between traders and market managers during the development of a new local market at Pasar Pagi Betung, Banyuasin Regency. The development of the new local market, which aims to improve the organization and function of traditional markets, has instead given rise to various social and economic problems for traders. The conflict stems from unequal power relations, limited involvement of traders in policy-making processes, and differences in economic access between traders who remain in the old local market and those who occupy the new local market. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with traders, market managers, and representatives of government agencies responsible for market management, and was supported by field observations and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the conflict reflects the command-obey-class relationship as explained in Ralf Dahrendorf's conflict theory, where market managers and the government have policy authority, while traders are in a position to adapt to these decisions. The impacts of the new local development are felt unevenly, including decreased income, insecurity, and unequal economic opportunities. This study concludes that conflict is a consequence of a development process that is not fully participatory, necessitating more inclusive and equitable conflict management.